Thoracic surgeryEarly and late results of the Nuss operation for pectus excavatum – a single institution experience - Pawlak, Krystian; Zieliński, Paweł; Gabryel, Piotr; Gałęcki, Bartłomiej; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: The purpose of this study was to evaluate the results of operative treatment of pectus excavatum using the Nuss method, with particular emphasis on the surgical technique used. Material and methods: Between 2002 and 2010, 622 patients (mean age 18.2) underwent surgical correction for pectus excavatum. One Nuss bar was implanted in 317 patients, two plates in 296, and 3 in the remaining nine patients. Metal bars were removed after 2.5-3 years. Results: Good and very good corrective effect of the Nuss procedure was achieved in 593 (95.3%) patients. There was no mortality in the early postoperative period. Transient and minor complications occurred in 213 (34.24%) patients – the most frequent were pneumothorax and pleural effusion (22,5%). An asymmetric funnel chest deformity, a complex deformity, reoperation after previously performed corrective surgery, operative time exceeding 60 min, age above 18 years, more than one implanted corrective plate and gender had significant influences on the occurrence of complications in the postoperative period. Conclusions : 1. The Nuss minimal invasive procedure is very effective and provides very good long-term results in the treatment of pectus excavatum. 2. The use of video-thoracoscopic control during insertion of implanted bars may prevent potential damage to the mediastinal organs. 3. In patients below 18 years old the number of postoperative complications is significantly lower (p = 0.0025).